2013
DOI: 10.1002/app.40222
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and morphology of polyester/thermoplastic flour blends

Abstract: International audienceTwo maize flours (standard and waxy grades) were plasticized in an internal mixer with a constant amount of water and two glycerol contents. The resulting thermoplastic flours (TPFs) were characterized in dynamic oscillatory shear and creep/recovery rheometry. They displayed two different behaviors: the viscoelastic behavior of a high-molecular-weight polymer for the first one and a gel-like behavior for the second one. The TPFs were then mixed with a copolyester [poly(butylene adipate-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…The complex viscosity (|η * |) values of TPS/TiO 2 composites were very high in the entire range of frequencies (Figure 5), in agreement with previous studies (Della Valle et al, 1998;Deme et al, 2014;Ostafinska et al, 2017). The complex viscosities of TPS/TiO 2 exceeded the complex viscosity value for the pure TPS matrix.…”
Section: Rheological Propertiessupporting
confidence: 90%
“…The complex viscosity (|η * |) values of TPS/TiO 2 composites were very high in the entire range of frequencies (Figure 5), in agreement with previous studies (Della Valle et al, 1998;Deme et al, 2014;Ostafinska et al, 2017). The complex viscosities of TPS/TiO 2 exceeded the complex viscosity value for the pure TPS matrix.…”
Section: Rheological Propertiessupporting
confidence: 90%
“…In plasticized starch and in plasticized starch/thermoplastic blends, where the amount of glycerol is typically 33-36 wt% to see if the difference in the envelope strength can still be detected in compounding conditions. We recently showed that the rheological behavior and the morphology of plasticized flour/thermoplastic blends were determined by the amylose/amylopectin ratio, the plasticizer content and the processing conditions, as for plasticized starch/thermoplastic blends (Demé et al, 2014). Becker et al (2001) studied the influence of a thermal treatment with glycerol stearate on various starches.…”
Section: Rheological Measurements During Starch and Flour Swellingmentioning
confidence: 99%